Hepatitis B Virus Infection Alters Gut Microbiota Composition in Mice - Zhu, Qingfeng; Xia, Panpan; Zhou, Xin; Li, Xiaoran; Guo, Weina; Zhu, Bin; Zheng, Xin; Wang, Baoju; Yang, Dongliang; Wang, Junzhong (Frontiers in Cellular and Infection Microbiology, 2019)
Gut microbiota composition is known to be associated with the progression of hepatitis B virus (HBV)-related liver cirrhosis in humans, outcome of HBV infection in mice, and seroconversion of HBV e-antigen in nucleot(s)ide analog-treated patients. The dynamic alteration of the gut microbiota following HBV infection is still unknown. In this study, a hydrodynamic injection mouse model mimicking acute or chronic HBV infection in humans with comparable virological and immunological features was used. The composition of gut microbiota in the control mice and mice with acute or chronic HBV infection was analyzed at different time points using the Illumina MiSeq platform. The expression of immune molecules in the colon was detected by real-time polymerase chain reaction. We found that the changes in gut microbiota composition, including the total operational taxonomic unit (OTU) count and Shannon-Weaver index, were significantly delayed in mice with HBV infection. Furthermore, the ratio of Bacteroidetes and Firmicutes was stable in the control mice, whereas remarkable dynamic patterns were observed in mice with HBV infection. Interestingly, the dynamic changes in Lactobacillus and Bifidobacterium were found to differ in acute or chronic HBV infection. In addition, the expression of IFN-γ and PD-L1 in the colon was found to be up-regulated early in mice with acute HBV infection, whereas the expression of PD-L1 in the colon of mice with chronic HBV infection was up-regulated later. These data indicate that HBV infection could hamper the development of the gut microbiota community and dynamically change the gut Firmicutes/Bacteroidetes ratio. These data improve our understanding of the relationship between gut microbiota and HBV infection.